Impact of educational nursing program on reducing the level of anxiety and complications among patients undergoing cardiac catheterization - Aboel-Kassem F. Abdelmegid, Mohamed; Zaki Azer, Sahra; Youssef Sayed, Samia; Mohamed Youness, Hanan; Abd Elal thabet, Reda (International Journal of Advanced Nursing Studies, 2018)
The current studyAimed: to identify the impact of implementing an educational nursing program on reducing the level of anxiety and complications among patients undergoing cardiac catheterization.Design: quasi-experimental design was used in this study. Setting: the Current study was conducted atAssiutUniversityHospital in the cardiac catheterization unit.Subjects: 60 adult patients, age between 20 – 65 years, male and female, thirty for each group (study and control). The group of patients who received educational nursing program was considered a study group, while who received a routine care was the control group. Tools: four.Tools: Structure Interview Questionnaire sheet, Hamilton Anxiety Rating Scale, Assessment of complications, & educational nursing program.Results: there was the statistically significant difference between both groups regarding the level of anxiety and incidence of local complications.Conclusion: giving written nursing program for patients more effective in decreasing level of anxiety for patients in the study group than the control group patients.Recommendations: Permanent attendance of a specialized nurse in the cardiac catheterization unit is of great importance to instruct and apply the guidelines of the patients. Simple illustration booklet and pamphlets must be adequate and available for patients with Arabic explanation that helps the patient how to live safely.